ผลของโปรแกรมการให้ความรู้ร่วมกับการให้ข้อมูลในการมีส่วนร่วมของครอบครัวต่อพฤติกรรมการดูแลทารกป่วยด้วยโรคปอดอักเสบของมารดา - คณิต ณ พัทลุง (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
The quasi-experimental research aimed to compare men score of maternal caring behaviors for infant with pneumonia before and after participated in this study and between maternal who received education provision and family participation information program and those who received conventional nursing care. Subjects were 40 mothers who caring on infants with pneumonia, age between 1 month to 1 year. They were equally assigned into 2 groups by matching age ,education, and experience of caring on infants with other respiratory system diseases or pneumonia, 20 in each group. The experimental group received education provision and family participation information program and the control group received conventional nursing care .The instrument for collecting data consisted of the caring behavior questionnaire with interview guide which had a CVI of .97 and the Cronbach’s alpha coefficient reliability of .84.Data were analyzed by mean, standard deviation ,and t-test. The major findings were as follows: 1. The mean score of maternal caring behaviors for infant with pneumonia after received education provision and family participation information program was significantly higher than before receiving the program at a level of .05. 2. The mean score of maternal caring behaviors for infant with pneumonia who received education provision and family participation information program was significantly higher than those who received conventional nursing care at a level of .05.